(3GdceGds - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOG fSJYjf Hg Ydi GdMbhEfG bO YQafG ZQVfG HcTa GdMb s
(3BNQgG (B:s
(3hGYde Cf MLQfG dGjONd Ydjg OGNd hdG jNQL efg NGQL aGage Ef TGA Gddg hYdjg JhcdJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B176 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGQ Gddg HGSJGfHhd (B(1641) s
Keywords: (3GdcjejGA h GdWHjYjGJs